A Review of Ghana’s E-health Strategy - Afagbedzi, Seth Kwaku; Obuobi, H.; Aryeetey, R.; Bosomprah, S. (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Ghana has been faced with weak health systems leading to preponderance of communicable diseases, under-nutrition, and poor reproductive health resulting in difficulties in meeting some of the targets of the MDGs. There are also increasing incidence of non-communicable and chronic diseases, and severe inequities in access to health services resulting in large disparities in health outcomes across the country.  In light of these, the Ministry of Health and Ghana Health Service in 2007 developed a National Health Policy which has three broad objectives. These are:(a)  To ensure that people live long, healthy and productive lives and reproduce without an increased risk of death.(b)  To reduce the excessive risk and burden of morbidity, mortality and disability, especially in the poor and marginalized groups(c)   To reduce inequalities in access to health, reproduction and nutrition services.However, achieving these objectives require a change in the way health business is run and that the health sector must find new and innovative ways of reaching more people with information and resources to help them make informed decisions. Under these circumstances the Ministry of Health and its agencies have identified e-health as the best means to achieve the above objectives and hence formulation of Ghana’s e-health strategy in 2010. The research seeks to: give an overview of the 2010 Ghana e-health strategies as a driving force in achieving the health sector goals; enumerate success chalked from implementation of e-health strategies; identify the barriers to the implementation of e-health strategies in Ghana.Methods: Ghana’s e-health policies and strategies since 2003 have been reviewed. Situational analysis approach was used in this review. Several stakeholders such as the Ministry of health, Ghana health service, Development partners, National Information Technology Agency, Academia, Telcos etc were consulted and they made very valuable contributions to this review. Results: Within 10 years Ghana has seen the development of five documents on e-health policies and strategies: ICT for Accelerated Development (ICT4AD) Policy; Proposals for Ghana eHealth Strategy; Health Sector’s ICT Policy and Strategy; ehealth plan: 2007-2011 and Ghana E-health strategy 2010.  Ghana’s 2010 e-health strategy seeks to: streamline the regulatory framework for health data and information management; build sector capacity for wider application of e-health solutions in the health sector; increase access and bridging equity gap in the health sector through the use of ICT and develop strategies towards paperless records and reporting systems. Ghana has chalked some success since the implementation of e-health strategies which are categorised as (1) Capacity building – Msc in Health Informatics; Certificate and Diploma in Health Informatics; e-learning project in all Health training institution. (2) mHealth initiatives - Sene smart phone project, MoTeCH, MVP Project – telemedicine, SMS for life, EWS, Fio-GHS and RDT smart reader. (3) Health Management Information Systems – LMIS, HIS, iHost (GHS), NHIA – eClaims, eRegister and DHIMS2.Conclusions: Full execution of this strategy is expected to lead to developing a robust ICT system to capture, store, exchange health information thereby improve patient care services throughout  the country and facilitating the achievement of the health sector goals.Keywords: E-health strategy, National Health Policy, Ministry of Health, Ghana Health Service